Análise microbiológica de incubadoras neonatais de uma maternidade de referência de Fortaleza - Ceará - Brito, Eva Anny Wélly de Souza (2023)
The neonatal incubator is a device that provides a favorable environment for the best development of the newborn and, when handled improperly, it can cause risks to the safety of newborns, such as health-related infections. Objectives: to carry out microbiological analysis of the incubators of a teaching maternity hospital in northeastern Brazil; identify the clinical profile of neonates using incubators; compare the Colony Forming Units (CFU) identified with the cleaning and disinfection time of incubators and allocation units; relate the microorganisms found in incubators with those of the most prevalent infections in neonatal intensive care units. Approved by the Ethics and Research Committee under opinion N0. 5,261,871. Primary, observational, exploratory, cross sectional study with a quantitative approach. Performed in Neonatal Intensive Care Unit and Conventional Neonatal Intermediate Care Unit. The incubators selected for the study were stratified into six groups according to the number of days of use, counting from the date of disinfection, being classified: group 1 clean incubators, without previous use; group 2 from one to three days; group 3 four to six days; group 4 from seven to nine days; group 5 from 10 to 12 days; group 6 from 13 to 15 days of use. The collection was carried out from Monday to Friday for 30 days and was divided into three moments: evaluation of the eligible incubators, microbiological collection using the collection technique with swabs on the hatches and inner corners of the incubator surface, and data collection of the neonates who were allocated in the incubated. The processing of the collected samples was performed at the Bacteriology Laboratory of the Applied Group in Medical Microbiology (GrAMM). At the processing site, the samples were added to sterile saline, subsequently inoculated into plates containing chocolate agar culture medium (5% blood). Colonies grown on plates were counted, characterized and macroscopically differentiated. Afterwards, Gram staining was performed for each colony found on the plates and biochemical tests. The collected data were stored in a Microsoft Excel Windows 2010 database, processed and analyzed descriptively and analytically. Most newborns were male, with extreme prematurity, very low birth weight, Apgar in the first minute less than 7 and initial diagnosis of pneumopathies. The prevalence of the simultaneous use of two antibiotics was verified, especially Ampicillin and Gentamicin. Regarding the bacterial growth profile, there was bacterial growth after cleaning and disinfection, with a similar growth pattern between groups 1 to 3 and between groups 4 to 6. There was a statistically higher CFU growth in the hatches than in the inner corners. And coagulase negative Staphylococcus were more prevalent. There was a similarity between the cultures of patients hospitalized in the units and the bacterial profile found in this study. It is necessary to strengthen permanent education strategies regarding patient hygiene and handling. And the importance of the nurse in the development of good practices of prevention, control and combat of infections in the direct assistance to the NB, in research and teaching is emphasized.